Estrategias de marketing en Cellspa de la ciudad de Babahoyo. - Murrieta Torres, Cristina María (2022)
The Marketing Strategies in CellSpa of the city of Babahoyo, consists of an analysis of the level of marketing, they are carried out to obtain real and updated information to know the current relationship and the level of satisfaction of the clients with the company. And it is based on a marketing strategy that promotes the use of competitive advantages, increases business profits, retains existing customers and presents itself to potential customers as the best alternative to choose from; Problem-based is due to distribution, marketing, and segmentation factors related to marketing components such as the four Ps: price, product, promotion, and advertising that help make a profit contribution. This scenario indicates that a marketing strategy must be leveraged to develop marketing and customer segmentation with a focus on the company's competitiveness.